Extensive Myiasis infestation associated with Oral Squamous Cell Carcinoma: Report of two cases - Sudharani Biradar; Pranali Wankhede; Anita Munde; Safia Shaikh (Wolters Kluwer Medknow Publications, 2015)
Myiasis is the condition of infestation of the body by fly larvae (maggots). The deposited eggs develop into larvae, which penetrate deep structures causing adjacent tissue destruction. It is an uncommon clinical condition, being more frequent in tropical countries and hot climate regions, and associated with poor hygiene, suppurative oral lesions, alcoholism and senility. The diagnosis of Myiasis is basically made by the presence of larvae. The reported cases of oral Myiasis associated with oral cancer in the literature are few. This paper reports two cases of oral and maxillofacial Myiasis involving larvae in patients with squamous cell carcinoma in adult males. The condition was managed by manual removal of the larvae, one by one, with the help of forceps and subsequent management through proper health care.